El metaforları/II. Yeni şiiri - Yiğit, Görkem Gökçe (Fırat Üniveristesi, 2026)
Aklın mantıksal işleyişinden ziyade gerçeküstü ve metaforik söylemine daha fazla yönelen II. Yeni akımı ve akım şairleri anlam yerine imgelem söylemi, edebiyatlarının açarı olarak kullanmışlardır. Anlamı ve onun üstünü örten kapalı tavrı sürdürürken metafor ve mecazdan yararlanan II. Yeni şairlerinin elin metaforik söylemini hangi düzlem ve boyutlarda işledikleri anlatılmaya çalışılmıştır. Şiirin içsel zenginliğini yeni yorum, anlam ve boyuta taşımaya çalışan II. Yeni şairleri, el metaforunu kullanırken aktarmak istediklerini kendi iç seslerinde yoğurmakta bunu söze ve yazıya dökerken de üzerine bir süs ve gizem perdesi örtmektedir. Bu örtü okuyucunun bilgi, tecrübe, donanım ve yaşanmışlıklarıyla bir değerlendirmeye tabi tutulmakta ve şekillenmektedir. Şiirin alışılmış basmakalıbına, biçimine, türüne, içeriğine ve konusuna farklı yaklaşımlar getiren ekol şairleri kullandıkları metaforlarla da adeta bilinenin ötesine geçmeyi amaçlar. Hatta daha da farklı bir boyut kazandırarak geleneksel ve moderni aynı şiirin içinde dahi verme çabasına girer uyumsuzluğun yeni uyumunu ortaya koyarlar. Belli bir görüş ve savın arkasından gider diye vurulabilecek olan yaftalamaları göze alan, farklı uç fikirleri kendi dillerinden aktaran ekol şairleri belirlenen kalıplara sığmadıklarını gösterirler. Az kelime ile yoğun söylemin ve duygusal çığlığın verildiği edebi bir tür olan şiir, konunun farklı boyutlar ile gözlemlenmesine katkıda bulunacak tarzdadır. Şiirin derinlerde bir yerde saklı olan ben az konuşurum sen çok anla mottosunun metafor üzerinden verilmeye çalışılması türlere tek boyutlu yaklaşılmaması gerektiğini de ortaya koyar. Çalışma iki bölümde incelenmekte ilk bölümde metafor kavramının etkin olduğu alanlar ve bu alanların dil ile ilintisi anlatılmakta ikinci bölümde ise bir metafor olarak el kavramı ile bu metaforun kullanıldığı başlıklar ve bu başlıkların II. Yeni şiirine yansımaları verilmektedir.

II. Yeni movement and its poets, who tended more toward surreal and metaphorical discourse rather than the logical functioning of the mind, used imagery discourse as the key to their literature instead of meaning. While maintaining meaning and the obscure attitude that conceals it, the metaphorical discourse of the hand employed by the poets of the II. Yeni, who benefited from metaphor and figurative expression, has been attempted to be explained in terms of the planes and dimensions in which it was processed. The poets of II. Yeni, who sought to carry the internal richness of poetry to new interpretations, meanings, and dimensions, internalized what they wished to convey while using the hand metaphor, and while transforming it into speech and writing, they covered it with a veil of ornament and mystery. This veil is subjected to evaluation and shaped through the reader's knowledge, experience, background, and lived experiences. The poets of the movement, who brought different approaches to the conventional clichés, form, genre, content, and subject matter of poetry, almost aimed to go beyond the known through the metaphors they used. They even attempted to provide a further dimension by presenting the traditional and the modern within the same poem, revealing a new harmony of incompatibility. The poets of the movement, who accepted the labels that could be directed at them for following a certain view or argument and who conveyed radically different ideas through their own language, demonstrated that they could not fit into predetermined molds. Poetry, as a literary genre in which intense expression and emotional outcry are conveyed with few words, is of a nature that contributes to observing the subject from different dimensions. The attempt to convey, through metaphor, the motto hidden somewhere deep within poetry "I speak little, you understand much" also reveals that genres should not be approached in a one-dimensional manner. The study is examined in two sections: in the first section, the fields in which the concept of metaphor is effective and the relationship of these fields with language are explained; in the second section, the concept of the hand as a metaphor, the headings under which this metaphor is used, and the reflections of these headings in II. Yeni poetry are presented.
Hand metaphors/II. New poetry
Keywords: Türk Dili ve Edebiyatı